TEORI KOMUNIKASI HADITH - Syamsuri Syamsuri (Komunitas Dosen Dakwah Institut Agama Islam Negeri (IAIN) Palu, 2013)
Hadith becomes the media of communication about the power of khalilah who affirmed his power by the Hadith of the Prophet. Muslim community exerted their loyalty to the authority of Islamic teachings. Then, khalilah continued the authority of da'wah to strengthen and perpetuate his power. The support of Muslim from Arab tribes and peninsula drives the expansion of da'wah to the world. The